Digital Flipbook Media Based on the Megibung Tradition to Improve the Attitude of Mutual Cooperation in Pancasila Education - Nisa Iman Sari; Ida Bagus Gede Surya Abadi; Gusti Ngurah Sastra Agustika (International Journal of Language and Literature, 2025)
The problem encountered in the implementation of Pancasila Education in fourth-grade elementary school is the low ability of students to apply the value of mutual cooperation in the topic of maintaining solidarity and unity. Students tend to understand the concept only at the cognitive level but have not been able to implement this value in learning activities or in their daily lives. This study aims to develop a digital flipbook learning media based on the Megibung tradition that is valid, practical, and effective in improving students’ mutual cooperation attitudes. This study employed a research and development (R&D) approach using the ADDIE model. The research subjects consisted of experts and fourth-grade elementary school students. Data were collected using non-test methods, including observation sheets to measure students’ mutual cooperation attitudes, expert validation questionnaires, and student response questionnaires. The research instruments included validation sheets for content experts, instructional design experts, and learning media experts, as well as observation sheets and practicality questionnaires for the developed media. Data were analyzed using qualitative and quantitative descriptive analysis, along with statistical testing to determine the effectiveness of the developed media. The results indicate that the Megibung tradition–based digital flipbook media demonstrates a very high level of validity according to expert evaluations, is considered practical based on student trials, and is effective in improving students’ mutual cooperation attitudes during the learning process. Therefore, the Megibung tradition based digital flipbook can serve as an innovative alternative learning media to foster students’ mutual cooperation attitudes in Pancasila Education learning. The findings also imply that the integration of local culture into digital learning media can support the strengthening of character education and enhance student engagement in the learning process.